Importance of Judicial Communication in Civil Proceedings in Germany - Schmitt, Stephan (Journal of Law, 2018)
Two fundamental changes were introduced into civil procedure law at the beginning of XXI century with respect to the obligation of a judge to give directions and strengthening of the position of a mediator judge, meaning the authority of a judge to influence the parties to judicial proceedings and drive them to a settlement agreement. As a result of two new regulations the communication was strengthened both between a judge and the parties and the parties themselves. Hence, the role of a judge is no more limited only to leading the proceedings in accordance with established procedure and adoption of a well-reasoned decision, based on substantive law. A judge has more intensive communication with the parties before the resolution of a dispute, be it through a court decision or a settlement agreement reached between the parties. This paper is an attempt to describe the main consequences of the new regulations and explain the new role of a judge. The paper offers the justification that the terms of reference of a judge should be redefined through the expansion of the scope of his activities, what becomes particularly important in the sense of impartiality. The expanded scope of activities of a judge bears certain risks as well: on the one hand a judge is required to have direct communication with the parties and on the other - the parties are entitled to refuse this communication with a view to protection of their own interests - for instance, when a judge offers settlement conditions to the parties generating negative attitude of the parties towards him in doing so. The law offers a solution - to involve a dispute-reviewing judge and a mediator judge as different persons at different phases of case proceedings. The paper will also discuss the financial benefits of judges' decisions based on party consensus.